The Use of IoT on Smart Agriculture in the Philippines: A Narrative Review - Mastul , Al-Rashiff Hamjilani; Awae, Afdol; Bara, Zuraida Julhiji; Yaro, Yusuf (Bincang Sains dan Teknologi, 2023)
This study, focusing on the Philippines, explores the benefits of implementing IoT (Internet of Things) technologies in modern agriculture. The primary objectives are to assess the impact of IoT on crop monitoring, livestock tracking, weather monitoring, automated irrigation, precision steering, greenhouse automation, and field mapping. The research methodology involved an extensive review of the current literature on IoT applications in agriculture and interviews and surveys with farmers and agricultural experts in the Philippines. Data were collected and analyzed to understand IoT adoption's practical implications and challenges in various agrarian domains. The findings indicate that IoT technologies offer significant advantages in enhancing agricultural practices in the Philippines. IoT-based crop monitoring provides real-time data on environmental conditions, enabling farmers to optimize irrigation, fertilization, and pest control. Livestock tracking through IoT ensures animal well-being and efficient breeding practices. IoT-based weather monitoring aids in informed decision-making for crop protection and risk management. Automated irrigation using IoT sensors reduces water wastage while improving crop health. Precision steering systems enhance resource management during planting and harvesting. Greenhouse automation optimizes plant growth conditions and reduces manual labour. Field mapping via IoT allows for site-specific management, improving yield and sustainability. Despite the benefits, challenges like internet connectivity and initial investment remain, necessitating comprehensive strategies for IoT integration in Philippine agriculture.